The importance of pharmacist engagement in diagnostic stewardship - Kimberly C. Claeys; Daniel J. Morgan; Melissa D. Johnson (Cambridge University Press, 2024)
Diagnostic stewardship is increasingly recognized as a powerful tool to improve patient safety. Given the close relationship between diagnostic testing and antimicrobial misuse, antimicrobial stewardship (AMS) pharmacists should be key members of the diagnostic team. Pharmacists practicing in AMS already frequently engage with clinicians to improve the diagnostic process and have many skills needed for the implementation of diagnostic stewardship initiatives. As diagnostic stewardship becomes more broadly used, all infectious disease clinicians, including pharmacists, must collaborate to optimize patient care.